Marketing Value Chain Analysis of Corn as Animal Feed Material in Rea Village, Binuang District, Polewali Mandar Regency - Handayani, Sri Ratna; Jumriani Dambe; Hamsah (Tarjih : Agribusiness Development Journal, 2025)
This study aims to understand and analyze the marketing value chain of corn as animal feed in Binuang District, Polewali Mandar Regency. This study uses a qualitative Descriptive Analysis method with primary data collection through interviews and direct observation in the field, as well as secondary data through relevant literature reviews. Data analysis uses food supply chain network analysis to understand the corn marketing process from farmers to end consumers. The results of the study show that the corn supply chain in Rea Village involves several parties, including corn farmers, collectors, animal feed processing factories, and laying hen farmers with three supply chain flows. Analysis of food supply chain network data shows that the structure of the corn supply chain consists of several flows, namely product flow, financial flow, and information flow. This study also shows that corn production in Rea Village has great potential to increase farmers' income and meet market needs.